Pairwise strategy-proofness and self-enforcing manipulation - Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2005)
Strategy-proofness' is one of the axioms that are most frequently used in the recent literature on social choice theory. It requires that by misrepresenting his preferences, no agent can manipulate the outcome of the social choice rule in his favor. The stronger requirement of 'group strategy-proofness' is also often employed to obtain clear characterization results of social choice rules. Group strategy-proofness requires that no group of agents can manipulate the outcome in their favors. In this paper, we advocate 'effective pairwise strategy-proofness.' It is the requirement that the social choice rule should be immune to unilateral manipulation and 'self-enforcing' pairwise manipulation in the sense that no agent of a pair has the incentive to betray his partner. We apply the axiom of effective pairwise strategy-proofness to three types of economies: public good economy, pure exchange economy, and allotment economy. Although effective pairwise strategy-proofness is seemingly a much weaker axiom than group strategy-proofness, effective pairwise strategy-proofness characterizes social choice rules that are analyzed by using different axioms in the literature.
Keywords: 330; Soziale Wohlfahrtsfunktion; Prinzipal-Agent-Theorie; Gruppenentscheidung